2020
DOI: 10.1093/rheumatology/keaa080
|View full text |Cite
|
Sign up to set email alerts
|

Negative associations for fasting blood glucose, cholesterol and triglyceride levels with the development of giant cell arteritis

Abstract: Objectives To investigate metabolic features that may predispose to GCA in a nested case–control study. Methods Individuals who developed GCA after inclusion in a population-based health survey (the Malmö Preventive Medicine Project; N = 33 346) were identified and validated through a structured review of medical records. Four controls for every validated case were selected from the database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 26 publications
(32 reference statements)
1
16
0
Order By: Relevance
“…PD-L1 expression is dependent on glucose uptake and intracellular glycolytic activity (66,91,92). Large epidemiological studies demonstrate that body mass index and fasting blood glucose levels were negatively associated with the development of GCA (93,94), supporting the concept that low glycolytic activity promotes low PD-L1 expression, enabling uncontrolled autoimmunity.…”
Section: T Cell-dendritic Cell Interactionsmentioning
confidence: 94%
“…PD-L1 expression is dependent on glucose uptake and intracellular glycolytic activity (66,91,92). Large epidemiological studies demonstrate that body mass index and fasting blood glucose levels were negatively associated with the development of GCA (93,94), supporting the concept that low glycolytic activity promotes low PD-L1 expression, enabling uncontrolled autoimmunity.…”
Section: T Cell-dendritic Cell Interactionsmentioning
confidence: 94%
“…23 Wadström et al have also recently suggested a negative association between the levels of cholesterol and triglycerides with the subsequent occurrence of GCA in a population-based cohort. 24 Accordingly, the impact of statins on the occurrence of GCA in our study is most probably mediated through its anti-inflammatory effect rather than cholesterol-lowering effect. Our results suggest that statin users exhibit consistently lower incidence of developing GCA compared with their controls, supported by analysis of both any drug use and new drug use, and the dose-response pattern.…”
Section: Discussionmentioning
confidence: 57%
“… 23 Wadström et al have also recently suggested a negative association between the levels of cholesterol and triglycerides with the subsequent occurrence of GCA in a population-based cohort. 24 Accordingly, the impact of statins on the occurrence of GCA in our study is most probably mediated through its anti-inflammatory effect rather than cholesterol-lowering effect.…”
Section: Discussionmentioning
confidence: 57%
“…The aetiology of GCA is poorly understood, but associations with host and environmental factors have been investigated. Obesity and diabetes mellitus are negatively associated with GCA 43 – 45 , whereas exposure to different infections, particularly those that affect the respiratory system, is associated with an increased risk of GCA 46 , 47 . Studies on smoking have shown variable effects that range from a protective effect on GCA development in men to an association with increased risk of GCA in women 48 , 49 .…”
Section: Large Vessel Vasculitismentioning
confidence: 99%